Current considerations on Helicobacter pylori infection in children: A comprehensive review of the available evidence - M. Rogalidou; A. Papadopoulou (Microbiota in Health and Disease)
Infection with Helicobacter pylori (H. pylori) is usually acquired in childhood. The prevalence of H. pylori is largely related to socioeconomic status and living conditions, especially those characterized by overcrowding and poor hygiene, with a high rate of intrafamilial transmission. Despite the global decline of H. pylori infection in most areas, prevalence remains high in some other areas. In children, severe disease associated with H. pylori infection is rare. Standard triple therapy, ideally prescribed according to susceptibility to H. pylori, is still the most commonly used form of therapy. The antibiotic resistance rate is high and probably the main cause of eradication failure. Several other factors are also being investigated for their influence on eradication rates. This review summarizes relevant publications on H. pylori infection in children from April 2023 to March 2024.